Reducibility of nonlinear almost periodic systems of difference equations given on a torus - Martynyuk, D. I.; Perestyuk, N. A.; Samoilenko, A. M. (Ukrains’kyi Matematychnyi Zhurnal, 1994)
Sufficient conditions are established for the reducibility of a nonlinear system of difference equations x(x + 1) = x(1) + ω + P(x(t), t) + λ, where P(x, t) is a function 2π-periodic in x_i(i = 1,..., n) and almost periodic in t with a frequency basis α, to the system y(t + 1) = y(t) + ω.